A Generalized Wallis Formula
Abstract
This article generalizes the famous Wallis’s formula for k ≥ 0 , to an integral over the unit sphere Sn-1. An application to the integral of polynomials over Sn-1 is discussed.

One of Wallis formulas is

${\int }_{0}^{\text{2π}}{\mathrm{sin}}^{2k}\theta \text{d}\theta ={\int }_{0}^{\text{2π}}{\mathrm{cos}}^{2k}\theta \text{d}\theta =\frac{\left(2k\right)!2\text{π}}{{2}^{2k}{\left(k!\right)}^{2}}$

for $k\ge 0$ . This formula can be proved by various methods     including a repeated application of a reduction formula such as

${\int }_{0}^{\text{2π}}{\mathrm{sin}}^{k}\theta \text{d}\theta =\frac{k-1}{k}{\int }_{0}^{\text{2π}}{\mathrm{sin}}^{k-2}\theta \text{d}\theta$ . Note that $sin\theta$ and $cos\theta$ are coordinates

of a point on the unit sphere in R2. Since the above formula involves an integration over the unit circle in R2, its extension to higher dimensions is of interest.

For each $x=\left({x}_{1},{x}_{2},\cdots ,{x}_{n}\right)\in {R}^{n}$ , let $|x|={\left(\sum \text{ }{x}_{i}^{2}\right)}^{1/2}$ be its Euclidean norm. We call $\alpha =\left({\alpha }_{1},{\alpha }_{2},\cdots ,{\alpha }_{n}\right)$ , where ${\alpha }_{i}\ge 0$ are non-negative integers, a multi-index, and $|\alpha |=\sum |{\alpha }_{i}|$ its degree. Set $\alpha !={\alpha }_{1}!{\alpha }_{2}!\cdots {\alpha }_{n}!$ and ${x}^{\alpha }={x}_{1}^{{\alpha }_{1}}{x}_{2}^{{\alpha }_{2}}\cdots {x}_{n}^{{\alpha }_{n}}$ . Let $\text{ }{S}^{n-1}=\left\{\xi \in {R}^{n}:|\xi |=1\right\}$ be the unit sphere in Rn and $\text{d}\sigma$ be its surface measure. Let ${B}_{r}\left(a\right)=\left\{x\in {R}^{n}:|x-a|\le r\right\}$ stand for the ball of radius r centered at a. The gamma function is defined as $\Gamma \left(s\right)={\int }_{0}^{\infty }\text{ }{\text{e}}^{-t}{t}^{s-1}\text{d}t$ , for $s>0$ . The generalized Wallis’s formula is a special case of the following theorem.

Theorem 1 (i) ${\int }_{{S}^{n-1}}\text{ }{\xi }^{\alpha }\text{d}\sigma =0$ , if any ${\alpha }_{i}$ is odd. In particular, the integral equals zero if $|\alpha |$ is odd.

(ii) ${\int }_{{S}^{n-1}}\text{ }{\xi }^{2\alpha }\text{d}\sigma =\frac{\left(2\alpha \right)!2{\text{π}}^{n/2}}{{2}^{2|\alpha |}\alpha !\Gamma \left(n/2+|\alpha |\right)},\text{\hspace{0.17em}}|\alpha |\ge 0$ .

Setting ${\alpha }_{i}=k$ and ${\alpha }_{j}=0$ for $j\ne i$ in the theorem, the generalized Wallis’s formula follows

${\int }_{{S}^{n-1}}\text{ }\text{ }{\xi }_{i}^{2k}\text{d}\sigma =\frac{\left(2k\right)!2{\text{π}}^{n/2}}{{2}^{2k}k!\Gamma \left(n/2+k\right)},\text{\hspace{0.17em}}k\ge 0.$

Note that for $|\alpha |=0$ , (ii) is equivalent to the well-known formula

${\omega }_{n-1}=\frac{2{\text{π}}^{n/2}}{\Gamma \left(n/2\right)}$ (1)

where ${\omega }_{n-1}$ is the surface area of the unit sphere in Rn. Theorem 1 is interesting in its own right and has further applications. For example, for a polynomial

$p\left(x\right)={\sum }_{|\alpha |\le m}\text{ }{b}_{\alpha }{x}^{\alpha }$ of degree m, one may express ${\int }_{{B}_{r}\left(0\right)}\text{ }p\left(x\right)\text{d}x$ as a simple

polynomial of degree $n+m$ in r. In the following we use polar coordinates $x=\rho \xi ,\text{\hspace{0.17em}}\rho =|x|,\xi \in {S}^{n-1}$ .

$\begin{array}{c}{\int }_{{B}_{r}\left(0\right)}\text{ }\text{ }p\left(x\right)\text{d}x=\underset{|\alpha |\le m}{\sum }{b}_{\alpha }{\int }_{{B}_{r}\left(0\right)}\text{ }{x}^{\alpha }\text{d}x=\underset{|\alpha |\le m}{\sum }{b}_{\alpha }{\int }_{0}^{r}\text{ }{\rho }^{|\alpha |+n-1}\text{d}\rho {\int }_{{S}^{n-1}}\text{ }{\xi }^{\alpha }\text{d}\sigma \\ =\underset{2|\alpha |\le m}{\sum }\frac{{b}_{2\alpha }{r}^{2|\alpha |+n}}{2|\alpha |+n}{\int }_{{S}^{n-1}}\text{ }{\xi }^{2\alpha }\text{d}\sigma =\underset{|\alpha |\le \left[m/2\right]}{\sum }\frac{{b}_{2\alpha }{d}_{\alpha }}{2|\alpha |+n}{r}^{2k+n}\\ =\underset{k=0}{\overset{\left[m/2\right]}{\sum }}\left(\underset{|\alpha |=k}{\sum }\frac{{b}_{2\alpha }{d}_{\alpha }}{2k+n}\right){r}^{2k+n}=\underset{k=0}{\overset{\left[m/2\right]}{\sum }}\text{ }{c}_{k}{r}^{2k+n}.\end{array}$

Here ${d}_{\alpha }={\int }_{{S}^{n-1}}\text{ }{\xi }^{2\alpha }\text{d}\sigma$ as given by (ii), and [.] is the bracket function.

Proof of Theorem 1. (i) The proof is by induction on $|\alpha |$ .

If $|\alpha |=1$ then $\xi ={\xi }_{i}$ for some i. Therefore, ${\int }_{{S}^{n-1}}\text{ }{\xi }^{\alpha }\text{d}\sigma ={\int }_{{S}^{n-1}}\text{ }{\xi }_{i}\text{d}\sigma =0$ by the symmetry of the sphere.

Assume now the assertion is true for $|\alpha |\le m$ for some $m\ge 1$ . Let $|\alpha |=m+1$ and assume, without loss of generality, that ${\alpha }_{1}$ is odd. Applying the divergence theorem results in

$\begin{array}{c}{\int }_{{S}^{n-1}}\text{ }\text{ }{\xi }^{\alpha }\text{d}\sigma ={\int }_{{S}^{n-1}}\text{ }{\xi }_{1}\left({\xi }_{1}^{{\alpha }_{1}-1}{\xi }_{2}^{{\alpha }_{2}}\cdots {\xi }_{n}^{{\alpha }_{n}}\right)\text{d}\sigma \\ ={\int }_{{B}_{1}\left(0\right)}\frac{\partial }{\partial {x}_{1}}\left({x}_{1}^{{\alpha }_{1}-1}{x}_{2}^{{\alpha }_{2}}\cdots {x}_{n}^{{\alpha }_{n}}\right)\text{d}x.\end{array}$ (2)

If ${\alpha }_{1}=1$ , the last integral in (2) is zero. Otherwise, a conversion to polar coordinates in (2), yields,

$\begin{array}{c}{\int }_{{S}^{n-1}}\text{ }{\xi }^{\alpha }\text{d}\sigma =\left({\alpha }_{1}-1\right){\int }_{{B}_{1}\left(0\right)}\text{ }{x}_{1}^{{\alpha }_{1}-2}{x}_{2}^{{\alpha }_{2}}\cdots {x}_{n}^{{\alpha }_{n}}\text{d}x\\ =\left({\alpha }_{1}-1\right){\int }_{0}^{1}\text{ }{\rho }^{m+n-2}\text{d}\rho {\int }_{{S}^{n-1}}\text{ }{\xi }^{\beta }\text{d}\sigma =\frac{{\alpha }_{1}-1}{m+n-1}{\int }_{{S}^{n-1}}\text{ }{\xi }^{\beta }\text{d}\sigma ,\end{array}$

where $\beta =\left({\alpha }_{1}-2,{\alpha }_{2},\cdots ,{\alpha }_{n}\right)$ . The last integral is now zero, by the induction hypothesis.

ii) The proof is by induction on $|\alpha |$ .

For $|\alpha |=0$ , we must establish (1). Let ${e}_{n}={\int }_{{R}^{n}}\text{ }{\text{e}}^{-\text{π}{|x|}^{2}}\text{d}x\text{ }$ . Writing ${e}_{n}$ as a product of integrals and using polar coordinates in R2 followed by a change of variables, one obtains

$\begin{array}{c}{e}_{n}=\underset{i=1}{\overset{n}{\prod }}{\int }_{R}\text{ }{\text{e}}^{-\text{π}{x}_{i}^{2}}\text{d}{x}_{i}={\left({e}_{1}\right)}^{n}={\left({e}_{2}\right)}^{n/2}\\ ={\left({\int }_{0}^{\text{2π}}\text{ }\text{d}\theta {\int }_{0}^{\infty }r{\text{e}}^{-\text{π}{r}^{2}}\text{d}r\right)}^{n/2}={\left({\int }_{0}^{\infty }\text{ }{\text{e}}^{-u}\text{d}u\right)}^{n/2}=1.\end{array}$

We used a change of variable $u=\text{π}{r}^{2}$ in the previous integral. Converting to polar coordinates for Rn results in

$\begin{array}{c}1={e}_{n}={\int }_{{R}^{n}}\text{ }{\text{e}}^{-\text{π}{|x|}^{2}}\text{d}x={\omega }_{n-1}{\int }_{0}^{\infty }{r}^{n-1}{\text{e}}^{-\pi {r}^{2}}\text{d}r\\ =\frac{{\omega }_{n-1}}{2{\text{π}}^{n/2}}{\int }_{0}^{\infty }\text{ }{u}^{n/2-1}{\text{e}}^{-u}\text{d}u=\frac{\Gamma \left(n/2\right)}{2{\text{π}}^{n/2}}{\omega }_{n-1}.\end{array}$

Identity (1) follows immediately from the last equation.

Now suppose the claim is true for $|\alpha |=m$ . Let $|\alpha |=m+1$ . We may assume, without loss of generality, that ${\alpha }_{1}\ge 1$ . Applying the divergence theorem followed by a conversion to polar coordinates leads to

$\begin{array}{c}{\int }_{{S}^{n-1}}\text{ }{\xi }^{2\alpha }\text{d}\sigma ={\int }_{{S}^{n-1}}\text{ }{\xi }_{1}\left({\xi }_{1}^{2{\alpha }_{1}-1}{\xi }_{2}^{2{\alpha }_{2}}\cdots {\xi }_{n}^{2{\alpha }_{n}}\right)\text{d}\sigma ={\int }_{{B}_{1}\left(0\right)}\frac{\partial }{\partial {x}_{1}}\left({x}_{1}^{2{\alpha }_{1}-1}{x}_{2}^{2{\alpha }_{2}}\cdots {x}_{n}^{2{\alpha }_{n}}\right)\text{d}x\\ =\left(2{\alpha }_{1}-1\right){\int }_{{B}_{1}\left(0\right)}\text{ }{x}_{1}^{2{\alpha }_{1}-2}{x}_{2}^{2{\alpha }_{2}}\cdots {x}_{n}^{2{\alpha }_{n}}\text{d}x=\frac{2{\alpha }_{1}-1}{n+2m}{\int }_{{S}^{n-1}}\text{ }{\xi }^{2\beta }\text{d}\sigma ,\end{array}$

where $\beta =\left({\alpha }_{1}-1,{\alpha }_{2},\cdots ,{\alpha }_{n}\right)$ . Since $|\beta |=m$ , and using the fact that $\Gamma \left(s+1\right)=s\Gamma \left(s\right)$ along with the induction hypothesis, we get

${\int }_{{S}^{n-1}}\text{ }{\xi }^{2\alpha }\text{d}\sigma =\frac{2{\alpha }_{1}-1}{n+2m}.\frac{\left(2\beta \right)!2{\text{π}}^{n/2}}{{2}^{2|\beta |}\beta !\Gamma \left(n/2+m\right)}=\frac{\left(2\alpha \right)!2{\pi }^{n/2}}{{2}^{2|\alpha |}\alpha !\Gamma \left(n/2+|\alpha |\right)}.$

Cite this paper
Namazi, J. (2018) A Generalized Wallis Formula. Applied Mathematics, 9, 207-209. doi: 10.4236/am.2018.93015.
References

   Muller, C. (1966) Spherical Harmonics. Springer-Verlag Berlin Heidelberg.
https://doi.org/10.1007/BFb0094775

   Macrobert, T.M. (1948) Spherical Harmonics: An Elementary Treatise on Harmonic Functions with Applications. Dover Publications, New York.

   Stein, E. and Weiss, G. (1971) Introduction to Fourier Analysis on Euclidean Spaces. Princeton University Press, Princeton.

   Jeffrey, H. and Jeffrey, B. (1999) Methods of Mathematical Physics. 3rd Edition, Cambridge University Press, Cambridge.

Top